Fenomena Post-Trauma Stress Disorder dalam Novel-Novel Karya Ziggy Zezsyazeoviennazabrizkie - Rahma, Fauzia; Roekhan, Roekhan; Albaburrahim, Albaburrahim (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The phenomenon of Post-Traumatic Stress Disorder (PTSD) in the novels of Ziggy Zezsyazeoviennazabrizkie represents a research area that can realistically depict a person’s psychological condition. This study aims to describe the types of trauma, causal factors, and literary functions through a psychological literary analysis using a qualitative descriptive method, focusing on the novels di Tanah Lada, White Wedding, and San Francisco by Ziggy Zezsyazeoviennazabrizkie. The findings of this research indicate that the three protagonists from the three different novels are identified as experiencing PTSD trauma, caused by two factors: psychosocial and sociocultural. Furthermore, the study reveals the literary functions of story development, character development, and event creation. PTSD trauma is marked by exposure to painful or stressful events, the presence of intrusive symptoms following the traumatic events, continuous avoidance of stimuli related to the traumatic experience, and other related symptoms. Psychosocial causal factors include parental deprivation and a pathogenic family structure, while sociocultural factors involve social roles and social changes. The literary functions within the novels include story development, character development, and event creation. These three key themes show that the three different novels by the same author are interconnected, reflecting the psychological abnormalities of PTSD in the lives of the characters.